2022
DOI: 10.26451/abc.09.01.11.2022
|View full text |Cite
|
Sign up to set email alerts
|

ManyBirds: A multi-site collaborative Open Science approach to avian cognition and behavior research

Abstract: Comparative cognitive and behavior research aims to investigate cognitive evolution by comparing performance in different species to understand how these abilities have evolved. Ideally, this requires large and diverse samples; however, these can be difficult to obtain by single labs or institutions, leading to potential reproducibility and generalization issues with small, less representative samples. To help mitigate these issues, we are establishing a multi-site collaborative Open Science approach called Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 58 publications
0
28
0
Order By: Relevance
“…The Many X projects aim to be inclusive, inviting collaboration between academics and nonacademics, across the world with clear, coherent, and accessible frameworks for research participation. The ManyBirds Project, in particular, aims to facilitate collaboration with a variety of potential sites, including zoos, labs, field, and private homes, by selecting experimental designs that are low time and labor intensive, requiring no/minimal physical contact with the experimenter and therefore suitable for unhabituated/untrained birds (Lambert et al, 2021). An example of this is the upcoming ManyBirds study on neophobia in birds—following a similar protocol as the above hornbill pilot study (for more information: Twitter: @TheManyBirds; Website: http://www.themanybirds.com).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Many X projects aim to be inclusive, inviting collaboration between academics and nonacademics, across the world with clear, coherent, and accessible frameworks for research participation. The ManyBirds Project, in particular, aims to facilitate collaboration with a variety of potential sites, including zoos, labs, field, and private homes, by selecting experimental designs that are low time and labor intensive, requiring no/minimal physical contact with the experimenter and therefore suitable for unhabituated/untrained birds (Lambert et al, 2021). An example of this is the upcoming ManyBirds study on neophobia in birds—following a similar protocol as the above hornbill pilot study (for more information: Twitter: @TheManyBirds; Website: http://www.themanybirds.com).…”
Section: Discussionmentioning
confidence: 99%
“…Contrast this to farms and laboratories that typically only house a handful of species or breeds (but with the obvious trade-off of increased sample sizes, Section 3). A recent review of avian cognition research (>500 articles across 30 journals from 2015 to 2020) indicated that only ~1.4% of bird species were represented, typically from four main orders (Lambert et al, 2021). It thus follows that only 3.9% of these studies were conducted in zoos (74.6% in labs; 17.4% at field sites; 3% at farms and 1.1% did not report the site or were at a mixture of sites; Lambert et al, 2021).…”
Section: Benefitsmentioning
confidence: 99%
See 1 more Smart Citation
“…We tested two conservation-relevant associated components of behavioural flexibility in a little-studied, Critically Endangered bird species, which could be further implemented across other species, for instance, through the ManyBirds framework [ 38 ], and used in applied sciences. Our findings help contribute to our understanding on how Bali myna and individuals react to changes in their environment.…”
Section: Discussionmentioning
confidence: 99%
“…We confirmed with keeping staff that these were suitably novel in all cases. The novel items were selected as such to be comparable with research in corvids [ 28 , 32 ], so the data may be useful for comparative research [ 38 ].
Figure 1 Novel objects.
…”
Section: Methodsmentioning
confidence: 99%